Entre limites e possibilidades : a intersetorialidade na rede de proteção da criança e do adolescente vítima de violência na cidade de Porto Alegre - Corrêa, Michele Cardoso (2018)
The objective of the present study is to know how the work of the child and adolescent victim of violence protection network in the Central, Islands and Humaitá region of Porto Alegre has been carried out in the perspective of the intersectoriality in order to identify alternatives for the qualification of the integral protection policies of this social segment. It was investigated how the phenomenon of violence with children and adolescents manifests itself in the protection network; what services, programs and policies are triggered; how the care, referrals and follow-ups are performed; how intersectoral actions are developed in the network for the protection of children and adolescent victims of violence; what strategies are used by professionals to face the challenges of this network; and which suggestions are listed by professionals to qualify the work from the perspective of intersectoriality. It is a qualitative study, based on the dialectical-critical method, developed through documentary research, which analyzed laws that guide the constitution of the rights of children and adolescents, and empirical research, which used the participant and systematic observation of thirteen (13) meetings held at the Centro, Ilhas and Humaitá protection network in the city of Porto Alegre, two (2) individual and semi-structured interviews with the region's guardian counselors and one (1) focus group with professionals working in the protection of children and adolescents, reaching a total of eighty-three (83) subjects. The information collected was analyzed through the content analysis technique of Bardin (2009) and the software QSR NVivo pro version 11. Through this study it is pointed out that children and adolescents were and remain the target of violence that worsens with the social inequalities generated by the capitalist mode of production, such as poverty, neglect, repression, neglect, sexual abuse, verbal, psychological, physical, institutional and structural violence. As a result of historical struggles to guarantee the human rights of children and adolescents, and in view of the country's participation in international pacts aimed to this rights, civilizational advances have been noted in the creation of legal and normative apparatuses that aim to face the violence against this population. The mapping of the protection network of the child and adolescent victim of violence in the city of Porto Alegre allowed identifying that the main public and social policies that comprise it are health, welfare, education, public security, human rights, justice policies, through of which several organs of protection of the child and the adolescent are articulated. As for the materialization of the intersectoriality in the network, the research evidenced concrete experiences of articulated work in order to contemplate the multiple demands that permeate the lives of users related to violence in childhood and adolescence. The information gathered points to the contradictory nature of the intersectoral approach, which allows for greater effectiveness in coping with violence against children and adolescents, and acts as a mechanism that hides the fragilities of the protection network. It was also evidenced that issues related to the precariousness of the working conditions and relationships of the protection network of child and adolescent has impact on social workers and also on users of services. Regarding the powers and possibilities of the network, it was possible to observe that the social workers who act in it share an ethical-political orientation directed towards a transformative societal project, guided by ideals such as the protection of the human rights of children and adolescents, better conditions life and work and other struggles absorbed from reality that strengthen their articulation as a collective subject participant in movements of resistance to the most diverse forms of violence.